Establishing Maritime Power Competitiveness Index: Benchmarking Indonesian Navy’s Aspiration to Become World-Class Sea Power - Tangguh Chairil; Ganesh Aji Wicaksono; Muthia Alvi Nurbaitty (Intermestic: Journal of International Studies, 2022)
As an archipelagic country, Indonesia has long envisioned developing its Navy (TNI AL) to become a world-class sea power. After its development was ruled out for a long period, the Minimum Essential Force published in 2010 mandates significant improvement in the Navy's strength. The doctrine of Global Maritime Fulcrum announced in 2014 also rests on maritime defense as one of its pillars, mandating the development of the Navy’s capability. Despite the grand vision, it is unclear to what extent the Navy has been developed to achieve this aim. This paper aims to answer this question by establishing a Maritime Power Competitiveness Index as a composite index for measuring the sea power of countries. Using the index, this paper then measures the Indonesian Navy's strength through the years to track the development of its capability and compares it with the navies of other rival countries.